Dual effect of selenium loaded chitosan nanoparticles on growth, antioxidant, immune related genes expression, transcriptomics modulation of caspase 1, cytochrome P450 and heat shock protein and Aeromonas hydrophila resistance of Nile Tilapia (Oreochromis niloticus). Issue 110 (March 2021) - Ibrahim, Doaa; Neamat-Allah, Ahmed N.F.; Ibrahim, Seham M.; Eissa, Hemmat M.; Fawzey, M.M.; Mostafa, Doaa I.A.; El-Kader, Shaimaa A. Abd; Khater, S.I.; Khater, Safaa I.
Abstract: Nowadays there is a great attention for nanotechnology in aquaculture production. It has an efficient role in nutrients and drugs delivery, ponds sterilization, water treatment and aquatic diseases reduction. Till now, there is no available data on impact of selenite-loaded chitosan nanoparticles (SeChNPs) on Nile tilapia. Hence, the current study investigated the effects of selenite-loaded chitosan nanoparticles supplementation on the growth, immune, antioxidant and apoptotic related genes as well as resistance to Aeromonas hydrophila of Nile tilapia, Oreochromis niloticus. A total of 400 fish were randomly divided into four groups, and each group retained five replicates. The control group was fed a basal diet (with inorganic se), other groups fed diets supplemented with SeChNPs 0.5, 1 and 2 g/kg diet. The loading concentration of Se to ChNPs was 0.3, 0.6 and 1.2 mg/0.5, 1 and 2 gm respectively. Fish groups fed SeChNPs (0.5 and 1 g/kg) exhibited the highest final body gain, better feed utilization. Additionally, the expression of myostatin gene was down-regulated by 0.2 and 0.3 fold in group fed 0.5 and 1 g/kg SeChNPs when compared with control group. Dietary inclusion of SeChNPs increased serum lysozyme, alternative complement and myeloperoxidase activities and immunoglobulin type M level. Supplementation of SeChNPs at the level of 2 g/kg up-regulated glutathione peroxidase, superoxide dismutase and catalase expression by 1.12, 4.9 and 2.31 folds respectively, in comparison with control group. In contrast, the levels of C- reactive protein and malondialdehyde were reduced. The expression of IL-10, IL-8, TNF-α and IL-1β genes was up-regulated after dietary inclusion of different levels of SeChNPs in a dose dependent manner. Post-challenge, the highest survival rate was detected in group fed 2 g/kg SeChNPs (93%) in contrast, the control group was displayed the lowest survival rate (45%). After challenge with A. hydrophila, the expression of caspase 1 was up-regulated in groups fed 1 and 2 g/kg of SeChNPs. Moreover, the maximum down-regulation of cytochromes P450 and heat shock protein were found in 2 g/kg SeChNPs supplemented group (reduced by 0.4 and 0.6-fold, respectively, when compared with control group). In conclusion, the ameliorative effects of SeChNPs on Nile tilapia growth resulted from immune stimulatory and free radicals scavenging effects of selenium loaded chitosan nano composite. Graphical abstract: Image 1 Highlights: A nanoparticle made with selenium and chitosan (SeChNPs) was used to stimulate fish growth and immune system. Fish growth was improved by SeChNPs and was proved by down-regulation of myostatin gene expression. Immune and antioxidant relevant genes were improved by SeChNPs. Down-regulation of caspase 1, P450 and HSP70 expression reduced apoptosis in Nile tilapia after A. hydrophila infection.